# Rewriting Expression

• Apr 12th 2007, 08:33 PM
classicstrings
Rewriting Expression
How do i rewrite, y = 30x/ (120-x) into y = (3600/(120-x)) - 30?
• Apr 12th 2007, 09:31 PM
Jhevon
Quote:

Originally Posted by classicstrings
How do i rewrite, y = 30x/ (120-x) into y = (3600/(120-x)) - 30?

y = 30x/(120 – 6)

= (3600 – 3600 + 30x)/(120 – x)

= 3600/(120 – x) + (30x – 3600)/(120 – x)

= 3600/(120 – x) + [30(x – 120)]/(120 – x)

= 3600/(120 – x) – 30(120 – x)/(120 – x)

= 3600/(120 – x) - 30
• Apr 12th 2007, 10:28 PM
earboth
Quote:

Originally Posted by classicstrings
How do i rewrite, y = 30x/ (120-x) into y = (3600/(120-x)) - 30?

Hi,

use long division:
Code:

3600
30x          ÷ (-x+120) = -30 + ----------
-(30x-3600)                        -x + 120
-------------
3600

• Apr 12th 2007, 10:29 PM
Jhevon
Quote:

Originally Posted by earboth
Hi,

use long division:
Code:

3600
30x          ÷ (-x+120) = -30 + ----------
-(30x-3600)                        -x + 120
-------------
3600

nice!
• Apr 12th 2007, 11:12 PM
classicstrings
Thank you both!